Urban Expansion in Damascus Rural Governorate - Case Study of the town of Sabaina during the period 1950-2011 - Fakoush, Oqba; Daghman, Riem (Latakia University Journal -Engineering Sciences Series, 2019)
الاستخدام المختلط للأراضي كأحد وسائل التّصميم العمراني لتحقيق الاستدامة الاجتماعيّة والاقتصاديّة في الضّواحي السّكنيّة عقبة فاكوش ريم دغمان إنّ الاستخدام المختلط للأراضي يجعل الضَّواحي السَّكنية الحديثة مكتفية ذاتياً ونابضة بالحيويَّة وجذَّابة، ويؤهّلها لتكون مراكز تنمويَّة ضمن محيطها العمراني الأوسع، ولكنَّ هناك غياب كبير لمثل هذا النَّوع من التَّصميم العمراني ضمن الضَّواحي السَّكنية الجديدة محليَّاً مما جعل الطَّابع السَّكني يغلب عليها وقلَّل من الأنشطة الاقتصاديَّة وتنوّعها، وهذا أدَّى بطبيعة الحال إلى ظهور حلول عشوائيَّة غير مدروسة ضمن السِّياق العام. يهدف هذا البحث إلى دراسة ومناقشة هذا النَّوع من الاستخدام الموصى به عالميّاً ومنعكساته العمرانيَّة والتَّصميمية بغية تحسين البيئة الحضريَّة اجتماعيّاً واقتصاديّاً، وذلك من خلال دراسة بعض أحدث الأمثلة العالميَّة وإجراء دراسة ميدانيَّة لبعض التَّطورات الجارية في الضَّواحي السَّكنية المحيطة بمدينة دمشق للوقوف على وضعها الرَّاهن وما طرأ عليها من تطورات، بغية الوصول إلى مجموعة من النَّتائج والتَّوصيات المفيدة لعمليات التَّصميم العمراني اللاَّحقة. The mixed use of land makes the modern residential suburbs self-sufficient and vibrant and attractive, and qualifies them to be development centers within the wider urban environment, while such a type of urban design is mostly absent within domestic new residential suburbs, which made the housing character dominated and minimized economic activities and diversity, This, of course, led to the emergence of random solutions that were not considered within the general context. This research aims to study and discuss this type of use which is globally recommended and its reflections on urban design and architectural design in order to improve the urban environment socially and economically, by studying some of the latest international examples and making a field study of some developments in the residential suburbs which surrounding Damascus city to develop a set of useful findings and recommendations for subsequent urban design.